An evaluation of the factors that influence the customer satisfaction in low cost airline service - Mohd Yussof, Siti Najwa; Sabar, Rohafiz (Universiti Utara Malaysia, 2019)
In view of the customer satisfaction in low Cost Airline service, the company airline has provide the best service quality for their customer to make sure that the customer always satisfied with the services. This research paper aims is to determine the passenger satisfaction in low cost carrier airline in Malaysia based on the service quality that airline industry provides for the customers. This research was identified the type factors that influences the passenger satisfaction in Low Cost Airlines in Malaysia. This study also focus on low cost carrier airline in Malaysia and to measure the service quality is very satisfied with the customer expectation. The data was analysed using correlation to determine the relationship between customer satisfaction and reliability, assurance and responsiveness.